Graphite material and preparation method thereof, negative electrode active material, negative electrode sheet, secondary battery, and electrical equipment

By combining graphite materials with different graphitization and aromaticity, the problem of low compaction density in long cycles is solved, and graphite materials with high energy density and good cycle performance are achieved.

CN119774599APending Publication Date: 2025-04-08XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411906808.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing graphite materials have low compaction density during long cycles and cannot meet the requirements of high volume energy density and mass energy density.

Method used

By combining the first graphite with a low graphitization degree with a high graphitization degree with a high graphitization degree, and preparing it with carbonaceous raw materials of different aromatic degrees, a graphite material with high compaction density and low expansion is obtained.

Benefits of technology

The high compaction density and good kinetic and cycling performance of graphite materials are achieved, meeting the needs of long cycle performance and high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774599A_ABST
    Figure CN119774599A_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery technology, and specifically discloses a graphite material and a preparation method thereof, a negative electrode active material, a negative electrode plate, a secondary battery, and an electrical device. The graphite material comprises a first graphite and a second graphite; the first graphite is prepared from a first carbonaceous raw material, and the second graphite is prepared from a second carbonaceous raw material; the aromaticity fa(A) of the first carbonaceous raw material is greater than the aromaticity fa(B) of the second carbonaceous raw material; the graphitization degree Gr(A) of the first graphite is less than the graphitization degree Gr(B) of the second graphite; wherein the aromaticity fa=A 1630 / (A 1630 +A 1438 +A 1335 );A 1630 1630cm in Fourier infrared spectrum ‑1 The peak intensity of infrared characteristic peak; A 1438 1438cm in Fourier infrared spectrum ‑1 The peak intensity of infrared characteristic peak; A 1335 1335cm in Fourier infrared spectrum ‑1 The peak intensity of infrared characteristic peaks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a graphite material and a preparation method thereof, a negative electrode active material, a negative electrode sheet, a secondary battery, and an electrical device. Background Art

[0002] With the development of the energy storage industry and market demand, the energy density requirements for energy storage batteries are getting higher and higher. In order to meet the needs of long cycles, existing graphite needs to be crushed into single particles, secondary particles or composite particles using low-aromatic raw materials, resulting in low compaction density of graphite prepared into negative electrode sheets and after one rolling, which cannot meet the requirements of high volume energy density and mass energy density. Therefore, it is urgent to provide a graphite material that can meet both compaction density and long cycle performance. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to provide a graphite material and a preparation method thereof, a negative electrode active material, a negative electrode sheet, a secondary battery, and an electrical device. The graphite material has a high compaction density, a high gram capacity, and a low overall expansion. The negative electrode active material containing the graphite material has good kinetic performance and cycle performance.

[0004] In one aspect of the present application, the present application provides a graphite material. According to an embodiment of the present application, the graphite material includes a first graphite and a second graphite;

[0005] The first graphite is prepared from a first carbonaceous raw material, and the second graphite is prepared from a second carbonaceous raw material;

[0006] The aromaticity fa(A) of the first carbonaceous feedstock is greater than the aromaticity fa(B) of the second carbonaceous feedstock;

[0007] The graphitization degree Gr(A) of the first graphite is less than the graphitization degree Gr(B) of the second graphite;

[0008] Wherein, the aromaticity fa=A 1630 / (A 1630 +A 1438 +A 1335 );

[0009] A 1630 1630cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peak; A 1438 It is 1438cm in Fourier infrared spectrum. -1 The peak intensity of infrared characteristic peak; A 1335 1335cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peaks.

[0010] The graphite material provided in the present application is obtained by compounding a first graphite with a lower graphitization degree and a second graphite with a higher graphitization degree, wherein the first graphite is made from a first carbonaceous raw material with a higher aromaticity; and the second graphite is made from a second carbonaceous raw material with a lower aromaticity, thereby ensuring that the graphite material has a high compaction density and low expansibility. Using it as a negative electrode active material can ensure a high compaction density while improving the kinetics and cycle performance of the material.

[0011] In some embodiments of the present application, the graphitization degree Gr(A) of the first graphite and the graphitization degree Gr(B) of the second graphite satisfy 0.5%≤Gr(B)-Gr(A)≤2%;

[0012] And / or, the graphitization degree Gr(A) of the first graphite satisfies 88%≤Gr(A)≤96%;

[0013] And / or, the graphitization degree Gr(B) of the second graphite satisfies 90%≤Gr(B)≤97%.

[0014] In some embodiments of the present application, the aromaticity fa(A) of the first carbonaceous feedstock satisfies fa(A)≥78%, and the aromaticity fa(B) of the second carbonaceous feedstock satisfies 65%≤fa(B)≤78%;

[0015] And / or, the aromaticity fa(A) of the first carbonaceous feedstock and the aromaticity fa(B) of the second carbonaceous feedstock satisfy 4%≤fa(A)-fa(B)≤14%.

[0016] In a second aspect of the present application, the present application proposes a method for preparing the graphite material described in the first aspect, comprising:

[0017] Grinding the first carbonaceous raw material and the second carbonaceous raw material respectively to obtain a first carbonaceous powder and a second carbonaceous powder;

[0018] Granulating the first carbonaceous powder to obtain a mixture;

[0019] Graphitizing the mixture and the second carbonaceous powder respectively to obtain a first graphite and a second graphite;

[0020] The first graphite and the second graphite are mixed to obtain the graphite material.

[0021] This results in a graphite material with high compacted density, high gram capacity and low overall expansion.

[0022] In some embodiments of the present application, the mixture satisfies at least one of the following conditions:

[0023] The particle size of the mixture is 1.5-2.2 times the particle size of the first carbonaceous powder;

[0024] The tap density of the mixture is 0.55-0.7 g / cm 3 .

[0025] In some embodiments of the present application, the temperature at which the second carbonaceous powder is graphitized is higher than the temperature at which the mixture is graphitized;

[0026] and / or, the mixture is graphitized at a temperature of 2400-3200° C.;

[0027] And / or, the temperature at which the second carbonaceous powder is graphitized is 2500-3300°C.

[0028] In some embodiments of the present application, the first graphite and the second graphite are mixed in a mass ratio of (2:8)-(6:4) to obtain the graphite material.

[0029] In the third aspect of the present application, the present application proposes a negative electrode active material. According to an embodiment of the present application, the negative electrode active material includes the graphite material described in the first aspect or the graphite material obtained according to the preparation method described in the second aspect. Thus, the negative electrode active material has good electrochemical performance.

[0030] In the fourth aspect of the present application, the present application proposes a negative electrode plate. According to an embodiment of the present application, the negative electrode plate includes the negative electrode active material described in the third aspect. Therefore, the negative electrode plate has all the advantages of the negative electrode active material, which will not be repeated here.

[0031] In the fifth aspect of the present application, the present application proposes a secondary battery. According to an embodiment of the present application, the secondary battery comprises the negative electrode sheet described in the fourth aspect. Thus, the secondary battery has good electrochemical performance.

[0032] In the sixth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the fifth aspect. Therefore, the electric device has all the advantages of the secondary battery, which will not be described in detail here.

[0033] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0035] Figure 1 The infrared spectrum of the negative electrode active material prepared in Example 1 of the present application is shown. DETAILED DESCRIPTION

[0036] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0037] In one aspect of the present application, the present application provides a graphite material. According to an embodiment of the present application, the graphite material includes a first graphite and a second graphite;

[0038] The first graphite is prepared from a first carbonaceous raw material, and the second graphite is prepared from a second carbonaceous raw material;

[0039] The aromaticity fa(A) of the first carbonaceous feedstock is greater than the aromaticity fa(B) of the second carbonaceous feedstock;

[0040] The graphitization degree Gr(A) of the first graphite is less than the graphitization degree Gr(B) of the second graphite;

[0041] Wherein, the aromaticity fa=A 1630 / (A 1630 +A 1438 +A 1335 );

[0042] A 1630 1630cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peak; A 1438 It is 1438cm in Fourier infrared spectrum. -1 The peak intensity of infrared characteristic peak; A 1335 1335cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peaks.

[0043] Carbonaceous materials 1630 The peak intensity corresponding to the C=C stretching vibration peak between aromatic hydrocarbons; A 1335 and A 1438 The peak intensity of the CH bending vibration peak corresponding to the saturated carbon methyl and methylene. The inventors found that A 1630The higher the peak intensity, the higher the C=C content in the raw material, the more benzene ring aromatic hydrocarbon structures, the more orderly the arrangement of carbon rings in the raw material during graphitization, the more complete the crystal form of the obtained graphite, and the fewer defects. Therefore, the graphite prepared from this carbonaceous raw material can be used with a high compaction density and a high gram capacity. However, the overly complete crystal form leads to a strong orientation of lithium insertion expansion of graphite and a large lithium insertion expansion of the pole piece. The orientation of graphite prepared from raw materials with low aromaticity is weak, so its orientation of lithium insertion expansion is weak, which can slow down the expansion of the pole piece. At the same time, certain defects can improve the dynamics of graphite. In addition, in order to reduce the problem of lithium insertion expansion caused by the use of raw materials with higher aromaticity, the lithium insertion expansion can be reduced by reducing its graphitization degree, but it will lead to an increase in defects on the surface of the particles, so it needs to be mixed with graphite with higher graphitization, thereby improving the overall cycle performance of the graphite material.

[0044] According to some specific embodiments of the present application, the graphitization degree Gr(A) of the first graphite and the graphitization degree Gr(B) of the second graphite satisfy 0.5%≤Gr(B)-Gr(A)≤2%. When the graphitization degree of the first graphite is too close to or higher than that of the second graphite, the expansion performance of the components is too deteriorated, and the second graphite cannot compensate for the loss of cycle performance caused by it.

[0045] According to some specific embodiments of the present application, the graphitization degree of the first graphite is 88% ≤ Gr(A) ≤ 96%, and the graphitization degree of the second graphite is 90% ≤ Gr(B) ≤ 97%. When the graphitization degree is within this range, both the compression enhancement effect brought by the first graphite and the expansion improvement effect brought by the second graphite can be taken into account. When the graphitization degree of the graphite is too low, the compression enhancement effect cannot be manifested, and when the graphitization degree is too high, the expansion and cycle performance deteriorate.

[0046] According to some specific embodiments of the present application, the aromaticity fa(A) of the first carbonaceous raw material satisfies fa(A)≥78%, and the aromaticity fa(B) of the second carbonaceous raw material satisfies 65%≤fa(B)≤78%. When the aromaticity fa of the first carbonaceous raw material is ≥78%, it means that the content of aromatics in the carbonaceous raw material is relatively high, and the crystallite size inside the graphite particles is relatively large after graphitization treatment.

[0047] The graphite crystal form is complete and the graphite compression density is high. The secondary particles can ensure high compression density and improve the dynamics of the material. However, the first graphite made from the first carbonaceous raw material with the above-mentioned aromaticity has a high crystallinity, and the particles expand greatly during the circulation process, causing serious damage to the SEI film. It is necessary to reduce the graphitization degree to reduce its lithium insertion expansion, but the reduction in graphitization degree will lead to an increase in graphite surface defects. The mixing of the second graphite with an aromaticity of 65-78% and a higher graphitization degree can further reduce the graphitization degree of the first graphite and improve the circulation performance of the graphite.

[0048] Specifically, the aromaticity fa(A) of the first carbonaceous feedstock may be 78%, 80%, 85%, 90%, etc.; the aromaticity fa(B) of the second carbonaceous feedstock may be 65%, 70%, 75%, 78%, etc.

[0049] According to some specific embodiments of the present application, the aromaticity fa(A) of the first carbonaceous raw material and the aromaticity fa(B) of the second carbonaceous raw material satisfy 4%≤fa(A)-fa(B)≤14%, thereby avoiding excessive difference in the aromaticity of the two raw materials. The first graphite can improve the compaction density of the graphite negative electrode material, and the second graphite can improve the expansion performance of the graphite negative electrode material.

[0050] In a second aspect of the present application, the present application proposes a method for preparing the graphite material described in the first aspect. According to an embodiment of the present application, the preparation method comprises:

[0051] Grinding the first carbonaceous raw material and the second carbonaceous raw material respectively to obtain a first carbonaceous powder and a second carbonaceous powder;

[0052] Granulating the first carbonaceous powder to obtain a mixture;

[0053] Graphitizing the mixture and the second carbonaceous powder respectively to obtain a first graphite and a second graphite;

[0054] The first graphite and the second graphite are mixed to obtain the graphite material.

[0055] The first carbonaceous raw material has a high degree of aromaticity, so the first graphite obtained has a high degree of crystallinity, and the particles expand greatly during the circulation process, which is easy to cause damage to the SEI film. Therefore, reducing the graphitization degree of the first graphite and performing granulation treatment can reduce its lithium insertion expansion. However, the reduction in graphitization degree and the introduction of binders in granulation will lead to an increase in its surface defects. By mixing with a second carbonaceous powder with a lower aromaticity but a higher degree of graphitization, the graphitization degree of the first graphite and the lithium source loss caused by the granulation treatment can be reduced, thereby improving the circulation performance of the graphite.

[0056] According to some specific embodiments of the present application, the D 50 As some specific examples, the D of the first carbonaceous powder is 7-10 μm. 50 The D of the second carbonaceous powder is 7 μm, 8 μm, 9 μm, 10 μm, etc. 50 As some specific examples, the D of the second carbonaceous powder is 8-13 μm. 50 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, etc.

[0057] According to some specific embodiments of the present application, the tap density of the first carbonaceous powder and the second carbonaceous powder is independently 0.5-0.7 g / cm 3 As some specific examples, the tap density of the first carbonaceous powder and the second carbonaceous powder may be independently 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 wait.

[0058] According to some specific embodiments of the present application, the granulation process further includes: mixing the first carbonaceous powder with a binder to obtain a mixture. Specifically, the type of the binder is not particularly limited, and those skilled in the art can select it according to the situation, including but not limited to asphalt.

[0059] According to some specific embodiments of the present application, the mass ratio of the first carbonaceous powder to the binder is 100:(0.5-15). As some specific examples, the mass ratio of the first carbonaceous powder to the binder may be 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14, 100:15, etc.

[0060] According to some specific embodiments of the present application, the granulation treatment is carried out at 400-700°C. As some specific examples, the granulation treatment is carried out at 400°C, 500°C, 600°C, 700°C, etc.

[0061] According to some specific embodiments of the present application, the mixture satisfies at least one of the following conditions:

[0062] The particle size of the mixture is 1.5-2.2 times the particle size of the first carbonaceous powder;

[0063] The tap density of the mixture is 0.55-0.7 g / cm 3 As some specific examples, the particle size of the mixture is 1.5 times, 2 times, 2.2 times, etc., of the particle size of the first carbonaceous powder; the tap density of the mixture is 0.55 g / cm 3 , 0.60g / cm 3 , 0.65g / cm 3 、0.70g / cm 3 wait.

[0064] According to some specific embodiments of the present application, the temperature at which the second carbonaceous powder is graphitized is higher than the temperature at which the mixture is graphitized. As some specific examples, the temperature at which the mixture is graphitized is 2400-3200°C, for example, 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C, 3100°C, 3200°C, etc.; the temperature at which the second carbonaceous powder is graphitized is 2500-3300°C, for example, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C, 3100°C, 3200°C, 3300°C, etc.

[0065] According to some specific embodiments of the present application, the first graphite and the second graphite are mixed in a mass ratio of (2:8)-(6:4) to obtain the graphite material. When there is too much first graphite in the graphite material, the pole piece will be too expanded when embedded with lithium, the SEI film will rupture quickly, and the cycle performance will decrease; when there is too much second graphite in the graphite material, the crystal form of the graphite is incomplete and there are too many defects, which will trigger more side reactions and lead to low initial coulomb efficiency of the battery, insufficient stability of the SEI film, and reduced cycle stability.

[0066] In the third aspect of the present application, the present application provides a negative electrode active material. According to an embodiment of the present application, the negative electrode active material includes the graphite material described in the first aspect or the graphite material obtained according to the preparation method described in the second aspect.

[0067] In a fourth aspect of the present application, the present application provides a negative electrode plate. According to an embodiment of the present application, the negative electrode plate includes the negative electrode active material described in the third aspect.

[0068] According to some specific embodiments of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.

[0069] According to some specific embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0070] According to some specific embodiments of the present application, the negative electrode active material includes the negative electrode active material described in the third aspect.

[0071] According to some specific embodiments of the present application, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0072] According to some specific embodiments of the present application, the negative electrode active material layer may further optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0073] According to some specific embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0074] According to some specific embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode active layer slurry; the negative electrode active layer slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0075] In a fifth aspect of the present application, the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes the negative electrode sheet described in the fourth aspect.

[0076] According to some specific embodiments of the present application, during the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte conducts ions between the positive electrode sheet and the negative electrode sheet. The isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet to prevent the positive and negative electrodes from short-circuiting while allowing ions to pass through.

[0077] According to some specific embodiments of the present application, the secondary battery is a lithium-ion secondary battery.

[0078] According to some specific embodiments of the present application, the positive electrode plate includes a positive electrode current collector, an intermediate coating and a positive electrode active material layer sequentially arranged on at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material and a lithium supplement. The positive electrode active material is preferably a lithium iron phosphate material.

[0079] According to some specific embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0080] According to some specific embodiments of the present application, the specific type of the positive electrode active material is not limited, and active materials known in the art that can be used for battery positive electrodes can be used, and those skilled in the art can select according to actual needs.

[0081] According to some specific embodiments of the present application, the positive electrode active material may include but is not limited to at least one of lithium transition metal oxides, lithium-containing phosphates of olivine structure and their respective modified compounds. Examples of lithium transition metal oxides may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their modified compounds. Examples of lithium-containing phosphates of olivine structure may include but are not limited to at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon and their modified compounds. These materials can all be obtained through commercial channels.

[0082] According to some specific embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0083] According to some specific embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0084] According to some specific embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the positive electrode sheet, such as the positive electrode active material, the lithium supplement agent, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone, NMP) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0085] According to some specific embodiments of the present application, the electrolyte may include an electrolyte salt and a solvent.

[0086] As an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0087] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0088] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0089] According to some specific embodiments of the present application, the present application has no particular restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. In some embodiments of the present application, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene (PE), polypropylene or polyvinylidene fluoride.

[0090] According to some specific embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a winding process or a lamination process.

[0091] According to some specific embodiments of the present application, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0092] According to some specific embodiments of the present application, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, polybutylene succinate, etc. can be listed.

[0093] In a sixth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the fifth aspect.

[0094] According to some specific embodiments of the present application, the secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, the electric toy can include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, an electric airplane toy, and the like, and the spacecraft can include an airplane, a rocket, a space shuttle, a spacecraft, and the like.

[0095] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0096] Example 1

[0097] 1. Preparation of positive electrode sheet:

[0098] The positive electrode active material lithium iron phosphate (molecular formula LiFePO4), the conductive agent acetylene black, and the binder polyvinylidene fluoride (abbreviated as PVDF) are fully stirred and mixed in a proper amount of N-methylpyrrolidone (abbreviated as NMP) solvent at a weight ratio of 96:2:2 to form a uniform positive electrode slurry; the slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet;

[0099] 2. Preparation of negative electrode sheet:

[0100] (1) Preparation of negative electrode active material:

[0101] Selecting a first carbonaceous raw material petroleum coke A having an aromaticity of 80.23% and a second carbonaceous raw material petroleum coke B having an aromaticity of 71.28%;

[0102] The first carbonaceous raw material is crushed and shaped to obtain D 50 8.5μm, tap density 0.6g / cm 3 The first carbonaceous powder is crushed and shaped to obtain D 50 11.8μm, tap density 0.58g / cm 3 a second carbonaceous powder;

[0103] The first carbonaceous powder was granulated and mixed with asphalt in a granulation kettle at a mass ratio of 100:5 in a 600°C temperature to obtain a mixture. The particle size of the mixture was controlled to be 14.7 μm and the tap density was controlled to be 0.57 g / cm 3 ;

[0104] The mixture and the second carbonaceous powder are graphitized respectively, and the graphitization temperature of the mixture is controlled at about 2900° C. to obtain the first graphite; the graphitization temperature of the second carbonaceous powder is controlled at 3050° C. to obtain the second graphite;

[0105] The first graphite and the second graphite are mixed in a mass ratio of 3:7 to obtain a negative electrode active material;

[0106] (2) Preparation of negative electrode sheet:

[0107] A negative electrode active material, a conductive agent, a thickener, a binder and a solvent are mixed in a solid content ratio of 96%:1%:1%:2% to obtain a negative electrode active layer slurry; a die head extrusion coater is used to coat the slurry on a negative electrode current collector with a conductive coating, and the slurry is dried to obtain an unrolled negative electrode sheet, and then the sheet is rolled by a roller press according to a designed compaction density to obtain a negative electrode sheet with a specific thickness;

[0108] 3. Preparation of electrolyte:

[0109] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:7, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L. Based on the above basic electrolyte, 2 wt% of fluoroethylene carbonate (FEC) is additionally added to prepare an electrolyte;

[0110] 4. Preparation of diaphragm:

[0111] PE porous polymer film is used as the isolation membrane;

[0112] 5. Battery assembly:

[0113] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order so that the separator is in the middle of the positive and negative electrodes to separate the positive and negative electrode sheets, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried battery. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.

[0114] Example 2

[0115] Compared with Example 1, the difference is:

[0116] The graphitization temperature of the first graphite is controlled at about 2980°C.

[0117] Example 3

[0118] Compared with Example 1, the difference is:

[0119] The graphitization temperature of the first graphite is controlled at about 2800°C.

[0120] Example 4

[0121] Compared with Example 1, the difference is:

[0122] The graphitization temperature of the second graphite is controlled at 3100°C.

[0123] Example 5

[0124] Compared with Example 1, the difference is:

[0125] The aromaticity of the second carbonaceous feedstock is 76.98%;

[0126] The graphitization temperature of the second graphite is controlled at 3000°C.

[0127] Example 6

[0128] Compared with Example 1, the difference is:

[0129] The aromaticity of the first carbonaceous raw material was 85.06%.

[0130] Example 7

[0131] Compared with Example 1, the difference is:

[0132] The first graphite and the second graphite are mixed in a mass ratio of 2:8 to obtain a negative electrode active material.

[0133] Example 8

[0134] Compared with Example 1, the difference is:

[0135] The first graphite and the second graphite are mixed in a mass ratio of 6:4 to obtain a negative electrode active material.

[0136] Example 9

[0137] Compared with Example 1, the difference is:

[0138] The aromaticity of the second carbonaceous feedstock is 65.70%.

[0139] Comparative Example 1

[0140] Compared with Example 1, the difference is:

[0141] The aromaticity of the first carbonaceous feedstock is 72.50%, and the aromaticity of the second carbonaceous feedstock is 93.10%.

[0142] Comparative Example 2

[0143] Compared with Example 1, the difference is:

[0144] The aromaticity of the second carbonaceous feedstock is 62.70%.

[0145] Comparative Example 3

[0146] Compared with Example 1, the difference is:

[0147] The graphitization temperature of the first graphite is controlled at about 3100°C.

[0148] The following tests were performed on the first carbonaceous raw material, the second carbonaceous raw material, the first graphite, the second graphite, the negative electrode sheet, and the battery in the embodiment and the comparative example respectively:

[0149] (1) Aroma test:

[0150] According to GB / T6040-2002 General Rules for Infrared Spectroscopic Analysis, the first carbonaceous raw material and the second carbonaceous raw material were tested by Fourier infrared spectroscopy, and the A of the carbonaceous raw material was measured according to the spectra. 1630 Value, A 1438 Value, A 1335 Value, according to fa = A 1630 / (A 1630 +A 1438 +A 1335 ) to obtain the aromaticity of each carbonaceous raw material;

[0151] (2) Graphitization degree test:

[0152] According to GB / T 24533-2019 lithium-ion battery graphite negative electrode materials, the first graphite and the second graphite are respectively tested for graphitization degree;

[0153] (3) Negative electrode compaction density test:

[0154] Place the negative electrode sheet under a roller press, roll it with a 20T rolling pressure, and then measure the thickness with a micrometer. Compacted density = (weight per unit area of ​​the negative electrode sheet - weight per unit area of ​​the copper foil) / (thickness of the electrode sheet - thickness of the copper foil);

[0155] (4) Battery cycle performance test:

[0156] Five lithium-ion batteries prepared in each of the examples and comparative examples were taken for cycle performance test, and the average value was taken. The lithium-ion battery was repeatedly charged and discharged through the following steps, and the discharge capacity retention rate of the lithium-ion battery was calculated.

[0157] First, in an environment of 25°C, the first charge and discharge were carried out. Constant-power charging was performed at a charging power of 1P until the upper limit voltage of 3.65V was reached, and then constant-voltage charging was performed. Then, constant-power discharge was performed at a discharge power of 1P until the lower limit voltage of 2.5V was reached. This was repeated twice, and the discharge capacity of the second cycle was recorded. Then, 1000 charge and discharge cycles were performed, and the discharge capacity of the 1000th cycle was recorded.

[0158] Capacity retention rate after 1000 cycles = (discharge capacity at the 1000th cycle / discharge capacity at the second cycle) × 100%.

[0159] The test results are shown in Table 1.

[0160] Table 1

[0161]

[0162] The results show that compared with the comparative example, the graphite material prepared in the embodiment can have both high compaction density and long cycle performance. Among them, the difference between the aromaticity fa(A) of the first carbonaceous raw material and the aromaticity fa(B) of the second carbonaceous raw material in Example 5 cannot satisfy 4%≤fa(A)-fa(B)≤14%, so the cycle life of the battery prepared therefrom is affected. Compared with Example 7, Example 8 is different only in that the mixing ratio of the first graphite and the second graphite is changed. When the mixing ratio of the two increases, the proportion of the first graphite becomes larger, which is more likely to cause excessive expansion of the lithium embedded in the pole piece, so the cycle performance decreases. Compared with Example 1, Example 9 is different only in that the aromaticity fa(B) of the second carbonaceous raw material is changed, resulting in a large difference between fa(A) and fa(B), so the cycle life of the battery prepared therefrom is affected. In addition, although the difference between fa(A) and fa(B) in Example 9 is too large, the compaction density of the overall material is low, so compared with Examples 4 and 8, the battery cycle performance is slightly improved. In addition, the difference between Comparative Example 1 and Example 1 is that the aromaticity of the first carbonaceous raw material is less than 78%, so the compaction density of the first graphite obtained is lower, and the gram capacity is lower, which in turn affects the compaction density of the overall material. Similarly, the difference between Comparative Example 2 and Example 1 is that the aromaticity of the second carbonaceous raw material is less than 65%, so the compaction density of the second graphite obtained is lower, and the gram capacity is lower, which in turn affects the compaction density of the overall material. The difference between Comparative Example 3 and Example 1 is that the degree of graphitization of the first graphite is higher than that of the second graphite, which does not affect the compaction density of the overall material, but easily causes the graphite to have a strong orientation for lithium insertion expansion, and the cycle performance of the prepared battery is poor.

[0163] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0164] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A graphite material, characterized in that: including a first graphite and a second graphite; The first graphite is prepared from a first carbonaceous raw material, and the second graphite is prepared from a second carbonaceous raw material; The aromaticity fa(A) of the first carbonaceous feedstock is greater than the aromaticity fa(B) of the second carbonaceous feedstock; The graphitization degree Gr(A) of the first graphite is less than the graphitization degree Gr(B) of the second graphite; Wherein, the aromaticity fa=A 1630 / (A 1630 +A 1438 +A 1335 ); A 1630 1630cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peak; A 1438 1438cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peak; A 1335 1335cm in Fourier infrared spectrum -1 The peak intensity of infrared characteristic peaks.

2. The graphite material according to claim 1, characterized in that The graphitization degree Gr(A) of the first graphite and the graphitization degree Gr(B) of the second graphite satisfy 0.5%≤Gr(B)-Gr(A)≤2%; And / or, the graphitization degree Gr(A) of the first graphite satisfies 88%≤Gr(A)≤96%; And / or, the graphitization degree Gr(B) of the second graphite satisfies 90%≤Gr(B)≤97%.

3. The graphite material according to claim 1, characterized in that The aromaticity fa(A) of the first carbonaceous feedstock satisfies fa(A)≥78%, and the aromaticity fa(B) of the second carbonaceous feedstock satisfies 65%≤fa(B)≤78%; And / or, the aromaticity fa(A) of the first carbonaceous feedstock and the aromaticity fa(B) of the second carbonaceous feedstock satisfy 4%≤fa(A)-fa(B)≤14%.

4. A method for preparing the graphite material according to any one of claims 1 to 3, characterized in that: include: Grinding the first carbonaceous raw material and the second carbonaceous raw material respectively to obtain a first carbonaceous powder and a second carbonaceous powder; Granulating the first carbonaceous powder to obtain a mixture; Graphitizing the mixture and the second carbonaceous powder respectively to obtain a first graphite and a second graphite; The first graphite and the second graphite are mixed to obtain the graphite material.

5. The preparation method according to claim 4, characterized in that: The D of the first carbonaceous powder 50 is 7-10 μm, and the D of the second carbonaceous powder is 50 8-13μm; And / or, the tap density of the first carbonaceous powder and the second carbonaceous powder is independently 0.5-0.7 g / cm 3 .

6. The preparation method according to claim 4, characterized in that: The granulation process further comprises: mixing the first carbonaceous powder with a binder to obtain a mixture; And / or, the mass ratio of the first carbonaceous powder to the binder is 100:(0.5-15); And / or, the granulation treatment is carried out at 400-700°C.

7. The preparation method according to claim 4, characterized in that: The mixture satisfies at least one of the following conditions: The particle size of the mixture is 1.5-2.2 times the particle size of the first carbonaceous powder; The tap density of the mixture is 0.55-0.7 g / cm 3 .

8. The preparation method according to claim 4, characterized in that: The temperature at which the second carbonaceous powder is graphitized is higher than the temperature at which the mixture is graphitized; and / or, the mixture is graphitized at a temperature of 2400-3200° C.; And / or, the temperature at which the second carbonaceous powder is graphitized is 2500-3300°C.

9. The preparation method according to claim 4, characterized in that: The first graphite and the second graphite are mixed in a mass ratio of (2:8)-(6:4) to obtain the graphite material.

10. A negative electrode active material, characterized in that: The invention comprises the graphite material according to any one of claims 1 to 3 or the graphite material obtained according to the preparation method according to any one of claims 4 to 9.

11. A negative electrode plate, characterized in that: Comprising the negative electrode active material according to claim 10.

12. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 11.

13. An electrical equipment, characterized in that: Includes the secondary battery as claimed in claim 12.

Citation Information

Cited By

  • Negative electrode material and preparation method and application thereof

    CN120922862A

  • Negative electrode material, preparation method and application thereof

    CN120922862B